CHARACTERISTICS OF KAMABOKO FROM CATFISH (CLARIAS GARIEPINUS) SURIMI PROCESSED WITH CARROT AND BEET ROOT AS FILLER AND NATURAL FOOD COLORANTS - Suryaningrum, Theresia Dwi; Irianto, Hari Eko; Ikasari, Diah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
The objective of the  study was to investigate  the effect of beet root  and carrot as filler and natural food colourant on the  chemical, physical  and sensory properties of kamaboko. Kamaboko from catfish (Clarias gariepinus) surimi was  processed with carrot (Daucus carota) and beet root (Beta vulgaris) at two concentrations (12 and 16%  of surimi weight). Assesment was done on chemical (proximate, pH), physical (folding test, WHC, gel strength and breaking force) properties as well as sensory evaluation. The results showed that kamaboko gel processed using beet root had better performance than kamaboko gel processed using carrot. Kamaboko processed  using beet root has protein content, folding test, water holding capacity, gel strength, breaking force, and sensory characteristics (appearance, colour, odor, texture, and taste)  better than kamaboko processed with carrot.  Increasing concentration of filler only affect on the gel strength and breaking force of kamaboko processed with beet root.  The best characteristic of kamaboko was obtained from kamaboko processed using beet root  with concentration of 12%. However, beet root was not recommended as colourant since the colour was not stable especially when stored at freezer.